Molecular and morphological description of a novel microsporidian Inodosporus fujiokai n. sp. infecting both salmonid fish and freshwater prawns. Issue 1 (13th January 2023) - Yanagida, Tetsuya; Asai, Nanami; Yamamoto, Michitaka; Sugahara, Kazuhiro; Fujiwara, Takuto; Shirakashi, Sho; Yokoyama, Hiroshi
Abstract: A new microsporidian disease of cultured rainbow trout Oncorhynchus mykiss has recently been confirmed in Japan, and the causative species was tentatively designated as Microsporidium sp. RBT-2021. Involvement of common prawn Palaemon paucidens in its transmission was suggested based on the previous feeding trials, although the microsporidian infection in P. paucidens was not confirmed. In this study, P. paucidens in Lake Biwa, Japan was investigated for microsporidian infection and 4 types of spores (types 1–4) were newly found. The nucleotide sequence of the small subunit ribosomal RNA gene was identical between type 1 and Microsporidium sp. RBT-2021, indicating they are conspecific. However, intriguingly, the spore morphology and the mode of development in fish and prawn were strikingly different. Morphological observations revealed type 1 in the prawn possesses characteristics of the genus Inodosporus Overstreet and Weidner, 1974, while Microsporidium sp. RBT-2021 in the trout exhibited the characteristics of the genus Kabatana Lom, Dyková and Tonguthai, 2000. In the phylogeny, type 1 was placed within a clade comprising Kabatana spp. and Inodosporus octosporus . Based on the morphological and molecular analyses, we describe Microsporidium sp. RBT-2021 as Inodosporus fujiokai n. sp. Together with the success of the previous prawn-feeding trials, this study strongly suggests I. fujiokai n. sp. has a multi-host life cycle utilizing fish and crustacean hosts and different modes of development in each host. Such polymorphic life cycle has barely been known among fish microsporidians. This study also suggests that the genus Kabatana is a junior synonym of the genus Inodosporus .